Local Regulation Drafting: Examining the Legislative Function of the Regional People’s Representative Council (DPRD) of Probolinggo City - Moh Fadillah Nur Rahmat (The Sunan Ampel Review of Political and Social Sciences, 2025)
The implementation of regional governance in Indonesia positions the Regional People’s Representative Council (DPRD) as a key actor in the exercise of regional autonomy, particularly through its legislative function in drafting regional regulations (Perda). This study aims to analyze how the Probolinggo City DPRD carries out its legislative function and to identify various obstacles that arise throughout the regulation-drafting process. Using a qualitative descriptive approach, data were collected through in-depth interviews with DPRD members, secretariat staff, and relevant stakeholders, as well as through a review of official documents. The findings indicate that although the procedural framework for drafting regional regulations has been clearly established, its implementation still encounters several challenges. The main issues include weak coordination between the legislative and executive bodies, limited human and technical capacity in preparing academic manuscripts and draft regulations, and low levels of public participation in the legislative process. These conditions affect both the quality of the policies produced and the effectiveness of the DPRD’s representative function in addressing community needs. This study recommends strengthening coordination mechanisms between the DPRD and local government, enhancing institutional capacity and the technical competence of members and expert staff, and expanding more inclusive and sustainable public participation channels in the drafting of regional regulations.